Cognitive Aspects of Depression in School-Age Children and Intervention Program - Βίγλιαρη, Ευαγγελία; Βασιλάκη , Ελένη; Σπαντιδάκης, Ιωάννης (Education Sciences, 2023)
In this paper we investigate the cognitive parameters of depression in childhood and we present some prevailing cognitive theories which try to record and explain the etiology and maintenance of depression. We also present a number of intervention programs based on these theories for the improvement of Autobiographical memory. These programs aim to cultivate resilience in childhood. Throughout the paper we demonstrate the consequences of depression as well as the imperative need to develop and implement intervention programs aimed mainly at the prevention of depressive symptomatology, and at the same time highlighting the lack of such programs in the Greek Education System.